1983
DOI: 10.1172/jci110929
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of 5-aminolevulinic acid and heme from 4,5-dioxovalerate in the rat.

Abstract: A B S T R A C T We previously demonstrated an alternate pathway for the biosynthesis of 5-aminolevulinic acid (ALA) in bovine liver mitochondria and of tetrapyrroles in suspensions of rat hepatocytes (1980. J. Biol. Chem. 255: 3742;. Proc. Natl. Acad. Sci. USA. 78: 5335). This pathway involves a transamination reaction that incorporates the intact 5-carbon skeleton of 4,5-dioxovaleric acid (DOVA) into ALA.We investigated this alternate pathway in vivo by the intraperitoneal injection of DOVA into rats. 3.4%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This alternative reaction was first described by the group of Varticovski, who isolated a pyridoxal-phosphate-dependent DOVA transaminase from bovine liver mitochondria [7]. Using radiolabelled DOVA, Morton and colleagues showed that DOVA transaminase-mediated formation of ALA can occur in liver cells [57] and whole animals [58]. Okuno and colleagues demonstrated the biosynthesis of ALA by DOVA transamination in the liver of rats, rabbits and humans, which further supported the potential in vivo importance of this alternative pathway for ALA synthesis [59].…”
Section: Metabolism Of γ δ-Dioxovalerate (Dova)mentioning
confidence: 99%
“…This alternative reaction was first described by the group of Varticovski, who isolated a pyridoxal-phosphate-dependent DOVA transaminase from bovine liver mitochondria [7]. Using radiolabelled DOVA, Morton and colleagues showed that DOVA transaminase-mediated formation of ALA can occur in liver cells [57] and whole animals [58]. Okuno and colleagues demonstrated the biosynthesis of ALA by DOVA transamination in the liver of rats, rabbits and humans, which further supported the potential in vivo importance of this alternative pathway for ALA synthesis [59].…”
Section: Metabolism Of γ δ-Dioxovalerate (Dova)mentioning
confidence: 99%
“…The glucose effect decreases 5‐ALA synthesis. Decreased production of heme decreases heme enzyme activity and causes a decline in the mitochondrial electron transfer system, which decreases consumption of glucose 16 . This leads to a further increase in glucose concentration in cells, which inhibits 5‐ALA production.…”
Section: Introductionmentioning
confidence: 99%
“…Insensitivity to insulin may be caused by a defensive reaction to protect 5‐ALA and heme synthesis. A resulting increase in glucose concentration may also occur in the diabetic patient, with a subsequent decrease in 5‐ALA synthesis, leading to a reduction in heme 16 . Preclinical and safety tests suggest that 5‐ALA is safe at modest doses 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and Safety Tests suggest that 5-ALA is safe at modest doses. A summary of these findings from investigations conducted by Cosmo Oil & SBI can be seen in Tables 2 and 4 [7,8]. In these studies, 3 different doses of 5-Aminolevulinic acid (5-ALA) phosphate, Sodium Ferrous Citrate (SFC) and Corn starch as filler were tested in humans.…”
Section: Studies Completedmentioning
confidence: 99%